Fassade eines städtischen Arbeiter-Wohnblocks (ca. 1940) - Senn, Paul
soziale Fragen;Raumplanung und Wohnungswesen;Ortschaft;Agglomeration;Stadt soziale Fragen;sozialer Rahmen;Sozialstruktur;soziale Schicht;Arbeiterschaft soziale Fragen;Raumplanung und Wohnungswesen;Wohnmilieu